2002
DOI: 10.1134/1.1491967
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study of the peculiar galaxy UGC 5600

Abstract: Abstract. We present our observations of the galaxy UGS 5600 with a long-slit spectrograph (UAGS) and a multipupil field spectrograph (MPFS) using the 6-m telescope of Special Astrophysical Observatory. Radial-velocity fields of the stellar and gaseous components were constructed for the central region and inner ring of the galaxy. We proved the existence of two almost orthogonal kinematic subsystems and conclude that UGC 5600 is a galaxy with an inner polar ring. In the circumnuclear region, we detected nonci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As pointed out by authors, taking into account the ring brightness, such value is somewhat lower than that expected by the metallicity-luminosity relation. A spectroscopic study of the peculiar galaxy UGC5600, classified as probable PRG (Whitmore et al 1990), by Shalyapina et al (2002) reports a quasi-solar metallicity for such object, 12+log(O/H) ∼ 8.8 = 0.9Z ⊙ , which is consistent with its high luminosity (M B = −19.4), but it is larger with respect to the values of other PRGs given before.…”
Section: -Metallicity-luminosity Relationmentioning
confidence: 67%
“…As pointed out by authors, taking into account the ring brightness, such value is somewhat lower than that expected by the metallicity-luminosity relation. A spectroscopic study of the peculiar galaxy UGC5600, classified as probable PRG (Whitmore et al 1990), by Shalyapina et al (2002) reports a quasi-solar metallicity for such object, 12+log(O/H) ∼ 8.8 = 0.9Z ⊙ , which is consistent with its high luminosity (M B = −19.4), but it is larger with respect to the values of other PRGs given before.…”
Section: -Metallicity-luminosity Relationmentioning
confidence: 67%
“…Some other works have determined the oxygen abundance in PRGs in order to test possible formation scenarios for these objects. For example, using an O/H– N 2 calibration, Shalyapina, Moiseev & Yakovleva () have found the oxygen abundance of 12+log(O/H) ∼ 8.8 dex for the PRG UGC 5600. Using a calibration between the electron temperature and strong oxygen emission lines, Brosch et al () have found that oxygen abundance in different regions of the apparent ring galaxy SDSSJ075234.33+292049.8 is 12+log(O/H) = 8.49 ± 0.08 dex.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the situation regarding spiral galaxies, as shown by van Zee et al (1998) as well as by Denicoló, Terlevich & Terlevich (2002), very few PRGs have been studied to determine their metal abundances. A few examples are UGC 5600 (Shalyapina, Moiseev & Yakovleva 2002) where no gradient was found, NGC 7468 (Shalyapina et al 2004) with an inverted gradient where the outer parts are more metal‐rich than the inner parts, and AM1934‐563 (Brosch et al 2007) with a normal gradient for the galaxy but a constant metallicity for the ring.…”
Section: Discussionmentioning
confidence: 99%